IMPLEMENTASI PENINGKATAN PROFESIONALISME GURU DI SEKOLAH - Nantara, Didit (Department of Mathematics Education , University of Jember, 2020)
This article aims to discuss some activities that can improve the professionalism of teachers in schools. The results of a survey conducted by PGRI regarding the impact of teacher professional certification on teacher performance show that the performance of teachers who have passed certification is still unsatisfactory and the performance of certified teachers is not satisfactory. Some of the activities of teachers in schools to improve their professionalism are making learning implementation plans, implementing student-centered learning strategies, carrying out an assessment of learning outcomes, self-development, carrying out scientific publications and innovative works, using learning media, and providing examples and guidance. Through some teacher activities at the school, the assumption that the results of the PGRI survey regarding the performance of certified teachers have not been satisfactory will be refuted or incorrect.